Studi Fenomenologi: Makna Ketidakpatuhan Wajib Pajak Importir - Pradnyarani Dewi, Anak Agung Istri; Mitrawan, Dwika Tirta (KRISNA: Kumpulan Riset Akuntansi, 2020)
This study is entitled "The Meaning of Non-Compliance of the Taxpayer Importers" using the Phenomenology Study of the Surabaya importer taxpayers. The aim is to uncover the meaning of the importer taxpayer regarding non-compliance in taxation. This type of research uses a qualitative approach to the study of phenomenology with an interpretive paradigm. The data used in the study of phenomenological studies are interview data. The data analysis technique used is the phenomenological analysis technique by Sanders (1982). The results of this study indicate that there are bad experiences experienced by importers regarding taxation and the existence of wholesale tax practices as a container to reap huge profits are the two main reasons why importers do not comply. Starting from a bad experience experienced by the informant, until in the end it caused disappointment and distrust again for the person working in the tax authority. The existence of wholesale tax practices as a forum for making large profits is also the main reason for the non-compliance behavior of importers. The synthesis of this research is that the role of the government, especially the DGT, is very influential in suppressing the non- compliance of importers taxpayers. Repairing the system as well as tightening the system is the right thing to overcome non- compliance.